The Genetic Landscape of Dystrophin Mutations in Italy: A Nationwide Study - Neri, Marcella; Rossi, Rachele; Trabanelli, Cecilia; Mauro, Antonio; Selvatici, Rita; Falzarano, Maria Sofia; Spedicato, Noemi; Margutti, Alice; Rimessi, Paola; Fortunato, Fernanda; Fabris, Marina; Gualandi, Francesca; et al. (Frontiers in Genetics, 2020)
Dystrophinopathies are inherited diseases caused by mutations in the dystrophin (DMD) gene for which testing is mandatory for genetic diagnosis, reproductive choices and eligibility for personalized trials. We genotyped the DMD gene in our Italian cohort of 1902 patients (BMD n=740, 39%; DMD n=1162, 61%) within a nationwide study involving 11 diagnostic centers in a 10-year window (2008-2017). In DMD patients, we found deletions in 57%, duplications in 11% and small mutations in 32%. In BMD, we found deletions in 78%, duplications in 9% and small mutations in 13%. In BMD, there are a higher number of deletions and small mutations are more frequent than duplications. Among small mutations that are generally frequent in both phenotypes, 44% of DMD and 36% of BMD are nonsense, thus eligible for stop codon read-through therapy; 63% of all out-of-frame deletions are eligible for single exon skipping. Patients were also assigned to Italian regions and showed interesting regional differences in mutation distribution. The full genetic characterization in this large, nationwide cohort has allowed us to draw several correlations between DMD/BMD genotype landscapes and mutation frequency, mutation types, mutation locations along the gene, exon/intron architecture and relevant protein domain, with effects on population genetic characteristics and new personalized therapies.